Validity of a food frequency questionnaire to assess nutritional intake among Sri Lankan adults - Jayawardena, R.; Byrne, N.; Soares, Mario; Katulanda, P.; Hills, A. (SpringerOpen, 2015)
Sri Lanka is undergoing nutritional transition and diet-related chronic diseases are emerging as an important health problem. Currently, no validated food frequency questionnaire (FFQ) exists to measure habitual dietary intake of Sri Lankan adults. The purpose of the study is to assess the validity of a semi-quantitative FFQ and 7-day weighed-intake dietary records (7DWR), designed to assess dietary intake among Sri Lankan adults. Dietary intake was measured using both a FFQ and 7DWR. The FFQ consisted of 8 food groups containing the main foods comprising the diet of Sri Lankan adults, a total of 85 items and 12 color photographs to identify serving size. One hundred healthy adults were randomly recruited from a community sample and administrated the FFQ followed by completion of the 7DWR. Paired sample t tests, Pearson’s correlation coefficients, kappa test and Bland–Altman analysis were conducted to determine correlation and the level of agreement for energy and micronutrients. Seventy-seven participants completed both the FFQ and 7DWR. Estimated mean energy intake (SD) from FFQ (1794 ± 398 kcal) and 7DWR (1698 ± 333 kcal, p < 0.001) were significantly different due to a significant overestimation of carbohydrate (11.5 g/day, p < 0.001) and to some extent fat (5.7 g/day, ns). Significant positive correlations (p < 0.05) were found between the FFQ and 7DWR for energy (r = 0.39), carbohydrate (r = 0.47), protein (r = 0.26), fat (r = 0.17) and dietary fiber (r = 0.32). Bland–Altman graphs indicated fairly good agreement between methods with no relationship between bias and average intake of each nutrient examined. Based on these findings, the FFQ appears to be an acceptable tool for assessing the nutrient intake of Sri Lankans and will assist proper categorization of individuals by dietary intake.